2022
DOI: 10.3390/biomedicines10071692
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic miR-506-3p Replacement in Pancreatic Carcinoma Leads to Multiple Effects including Autophagy, Apoptosis, Senescence, and Mitochondrial Alterations In Vitro and In Vivo

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a leading cause of cancer mortality. Considering its very poor prognosis, novel treatment options are urgently needed. MicroRNAs (miRNAs) are involved in the regulation of various physiological and pathological processes. In tumors, aberrant downregulation of given miRNAs may result in pathological overexpression of oncogenes, rendering miRNA replacement as a promising therapeutic strategy. In different tumor entities, miRNA-506-3p (miR506-3p) has been ambivalently de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…However, susceptibility to degradation by nucleases, low intracellular absorption rate due to an inherent negative charge and hydrophilic structure, and potential off-target effects limit the application of miRNAs ( Kara et al, 2022 ). MiRNA nanocarriers based on polymers, inorganic materials, and lipids have demonstrated their potential in the treatment of PC ( Arora et al, 2014 ; Gurbuz and Ozpolat, 2019 ; Gokita et al, 2020 ; Wu et al, 2020 ; Borchardt et al, 2022 ). However, it is important to note that therapeutic miRNAs can also accumulate in healthy tissues due to interstitial fluid pressure and shearing stress promoting NPs extravasation, which may lead to their degradation ( Zhang et al, 2019a ), and cause toxic and other adverse reactions ( Kara et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, susceptibility to degradation by nucleases, low intracellular absorption rate due to an inherent negative charge and hydrophilic structure, and potential off-target effects limit the application of miRNAs ( Kara et al, 2022 ). MiRNA nanocarriers based on polymers, inorganic materials, and lipids have demonstrated their potential in the treatment of PC ( Arora et al, 2014 ; Gurbuz and Ozpolat, 2019 ; Gokita et al, 2020 ; Wu et al, 2020 ; Borchardt et al, 2022 ). However, it is important to note that therapeutic miRNAs can also accumulate in healthy tissues due to interstitial fluid pressure and shearing stress promoting NPs extravasation, which may lead to their degradation ( Zhang et al, 2019a ), and cause toxic and other adverse reactions ( Kara et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…More particularly, miR-30c targets TWF1 and induces arrest of G1-phase of cell cycle and apoptosis, implying its role as a tumor0suppressive miRNA, while in cases where miR-30c was decreased, re-expression led to favorable anti-neoplastic effects [ 71 ]. MiR-340 overexpression is closely associated with the regulation of Bicaudal-D2 (BICD2), leading to the inhibition of pancreatic malignant cell growth and progression, implying the anti-neoplastic potential of miR-340/BICD2 axis [ 72 ].MiRNA-506 constitutes another miRNA that acts as tumor suppressor and significantly reduces the PDAC progression, although this is achieved when it is overexpressed [ 73 ].…”
Section: The Binary Role Of Mirnas In Pdacmentioning
confidence: 99%
“…It is reported that the replacement of miR-506-3p in PDAC has various effects on apoptosis, autophagy pathway, and on mitochondrial modifications not only in vitro but also in vivo. Based on the study of various pancreatic cancer entities, miRNA-506-3p was found downregulated in the majority of them (71%), whereas PIM-3 proto-oncogene was found overregulated [ 73 ]. Based on the above data, the downregulation of miR-506 expression was closely related to pancreatic tumor progression, with the less differentiated pancreatic tumors having a lower expression of miR-506, in comparison with moderate and well-differentiated tumors.…”
Section: The Interplay Of Autophagy and Mirnas In Pdacmentioning
confidence: 99%
See 2 more Smart Citations